2016
DOI: 10.1039/c6ra04098e
|View full text |Cite
|
Sign up to set email alerts
|

Bio-functionalized hybrid nanocomposite membranes for direct methanol fuel cells

Abstract: Featured methanol-blocking characteristics of nanocomposite membrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…The ester linkages and additional hydrogen bonds present within the cross-linked PVA structures are gradually degraded in the range of 160 °C. In this zone, all cross-linked PVA films are relatively stable, indicating that the thermal energy is not sufficient to break the ester linkages resulting from the reaction between the hydroxyl groups of the PVA and the carboxylic group of OA, hindering facile degradation (Mohanapriya et al 2016). Among the three cross-linked PVA networks, PVA/LA demonstrates the highest thermal stability because of the presence of functional groups that can actively participate in inter/intramolecular hydrogen bonding caused by the spatial proximity of the -COOH and -OH groups.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…The ester linkages and additional hydrogen bonds present within the cross-linked PVA structures are gradually degraded in the range of 160 °C. In this zone, all cross-linked PVA films are relatively stable, indicating that the thermal energy is not sufficient to break the ester linkages resulting from the reaction between the hydroxyl groups of the PVA and the carboxylic group of OA, hindering facile degradation (Mohanapriya et al 2016). Among the three cross-linked PVA networks, PVA/LA demonstrates the highest thermal stability because of the presence of functional groups that can actively participate in inter/intramolecular hydrogen bonding caused by the spatial proximity of the -COOH and -OH groups.…”
Section: Thermal Stabilitymentioning
confidence: 99%
“…On the other hand, amino acid forms electrostatic interactions with water molecules and held between –NH 2 + – and –COO − groups. These bridged water molecules form a hydration layer in the composite membrane acting as a vehicle for proton transport [111]. Thus, a small quantity of amino acid functionalized GO (1 wt.% in relation to SPEEK) brings significant improvement in proton conductivity.…”
Section: Carbon Nanomaterials As Additives In Pemsmentioning
confidence: 99%
“…This is in good agreement with the contact angle outcome. Nevertheless, the methanol uptake decreases slowly by the addition of SGO due to their less affinity on methanol 28,32,37 …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the methanol uptake decreases slowly by the addition of SGO due to their less affinity on methanol. 28,32,37 3.3.6 | IEC, proton conductivity, methanol permeability, and membrane selectivity IEC provides the available ionizable groups present in the membrane and indicates its capability to conduct protons. As seen in Table 3, it is clearly shown that the addition of SGO is enhanced by the IEC by means of increasing the SO 3 H density in the chitosan matrix which is accountable for the high mobility of the ionizable group.…”
Section: Water Uptake Swelling Ratio and Methanol Uptakementioning
confidence: 99%